A Success Story Leading Us to Think Big! - Jasmine Kamboj; Rahul Kamboj; Tejas Shah; Pam Khosla (Case Reports in Hematology)
Immune dysregulation is the hallmark of all autoimmune diseases. It is extremely interesting to study the associations and pathogenesis of the various autoimmune diseases, like the link between the AIHA and CLL. This link is well established and is based on the fact that there is loss of tolerance to the self-antigen, which in turn leads to immunebased hemolytic anemia. Around 30% of the patients with CLL are at the risk of developing AIHA, and 11% eventually develop AIHA. Whether there is any definite linkup between the corrupted immune system and “acute” leukemias/lymphomas is yet to be established. Needless to say, if there was an association between the pathogenesis of the ALLs and AIHA, it would be a landmark in the field of oncology as it would enforce early diagnosis and treatment for the disease which is much more aggressive and found in a comparatively younger age group (predominantly in children and a mean age of 40 years in adults) as compared to its chronic counterparts. The AIHA would serve as a “tip to the underlying iceberg” in these situations, warning us of the cryptic diagnosis.